2019
DOI: 10.1002/chem.201900732
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer Accompanied by the Oxidation of Adenosine

Abstract: Despite numerous experimental and theoretical studies, the proton transfer accompanying the oxidation of 2'-deoxyadenosine 5'-monophosphate 2'-deoxyadenosine 5'monophosphate (5'-dAMP, A)i ss till under debate. To address this issue, we have investigated the oxidation of A in acidic and neutral solutions by using transient absorption (TA) and time-resolved resonance Raman( TR 3 )s pectroscopic methods in combination with pulse radiolysis. The steadystate Raman signal of A was significantly affected by the solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Among those, reactions involving electron transfer along the DNA double strand have been investigated most frequently by experiments that focused on the kinetics and downstream analysis of radical products formed by reactions with solvent or other components in the reaction mixture. In contrast to electron transfer, proton transfer between an ionized and neutral nucleobase has been considered to occur in guanine–cytosine (G–C) and adenine–thymine (A–T) Watson–Crick pairs. Experimental studies of oligonucleotides tagged with oxidizable groups have revealed rapid deprotonation of guanine cation radicals. , Proton transfer between base pairs has been investigated in solution and studied in silico by density functional theory (DFT) calculations to indicate the proton recipient position. In a gas-phase study of the G–C cation radical complex, O’Hair and co-workers have utilized infrared multiphoton dissociation action spectroscopy to assign the ion structure as resulting from a proton transfer between the nucleobases . However, there have been few reports addressing the possibility of proton transfer along the DNA strand in cation radicals …”
Section: Introductionmentioning
confidence: 99%
“…Among those, reactions involving electron transfer along the DNA double strand have been investigated most frequently by experiments that focused on the kinetics and downstream analysis of radical products formed by reactions with solvent or other components in the reaction mixture. In contrast to electron transfer, proton transfer between an ionized and neutral nucleobase has been considered to occur in guanine–cytosine (G–C) and adenine–thymine (A–T) Watson–Crick pairs. Experimental studies of oligonucleotides tagged with oxidizable groups have revealed rapid deprotonation of guanine cation radicals. , Proton transfer between base pairs has been investigated in solution and studied in silico by density functional theory (DFT) calculations to indicate the proton recipient position. In a gas-phase study of the G–C cation radical complex, O’Hair and co-workers have utilized infrared multiphoton dissociation action spectroscopy to assign the ion structure as resulting from a proton transfer between the nucleobases . However, there have been few reports addressing the possibility of proton transfer along the DNA strand in cation radicals …”
Section: Introductionmentioning
confidence: 99%
“…A likely mechanism of adrenaline oxidation is the loss of an electron followed by rapid deprotonation. An intermediate radical is formed which loses a further electron to form the quinone product (32). (Figure 2B) compares the experimental results with theory.…”
Section: Mechanism Of Adrenaline Oxidationmentioning
confidence: 72%
“…Indeed, there are a number of notable examples of the application of time-resolved resonance Raman spectroscopy to pulse radiolysis from groups in the United States [6][7][8][9] and Japan. [10][11][12][13] However, we have focused on coupling the complementary technique of time-resolved infrared (TRIR) spectroscopy with pulse radiolysis, that is, PR-TRIR. While there were some early examples of PR-TRIR on gas-phase samples, 14,15 in 2010 we reported 16 the first application of nanosecond TRIR spectroscopy to the pulse radiolysis of liquid samples at our 9 MeV Laser Electron Accelerator Facility (LEAF), 17 which is part of the Accelerator Center for Energy Research (ACER) in the Chemistry Division at Brookhaven National Laboratory (BNL).…”
Section: Introductionmentioning
confidence: 99%